The long-run effects of neighborhood change on incumbent families - Nathaniel Baum-Snow; Daniel Hartley; Kwan Ok Lee (Center for Economic Studies and ifo Institute (CESifo), 2019)
A number of prominent studies examine the long-run effects of neighborhood attributes on children by leveraging variation in neighborhood exposure through household moves. How-ever, much neighborhood change comes in place rather than through moving. Using an urban economic geography model as a basis, this paper estimates the causal effects of changes in neighborhood attributes on long-run outcomes for incumbent children and households. For identification, we make use of quasi-random variation in 1990-2000 and 2000-2005 skill-specific labor demand shocks hitting each residential metro area census tract in the U.S. Our results indicate that children in suburban neighborhoods with a one standard deviation greater increase in the share of resident adults with a college degree experienced a 0.4 to 0.7 standard deviation improvement in credit outcomes 12-17 years later. Since parental outcomes are not affected, we interpret these results as operating through neighborhood effects. Finally, we provide evidence that most of the estimated effects operate through public schools.
Keywords: 330